One-Stage Complete Resection of Cholesteatoma With Labyrinthine Fistula: Hearing Changes and Clinical Outcomes. (April 2018) - Rah, Yoon Chan; Han, Won Gue; Joo, Jae Woo; Nam, Kuk Jin; Rhee, Jihye; Song, Jae Jun; Im, Gi Jung; Chae, Sung Won; Jung, Hak Hyun; Choi, June
Objectives: To evaluate long-term hearing changes and surgical outcomes for middle ear cholesteatoma with labyrinthine fistula following complete surgical removal of the cholesteatoma matrix. Methods: Consecutive samples of 43 patients who underwent 1-stage complete resection of the cholesteatoma matrix overlying a labyrinthine fistula were obtained. Immediate and long-term hearing changes were analyzed in association with fistula size. Accuracy of various diagnostic examinations was assessed. Results: Immediately postsurgery, the average bone conduction threshold (43.34 dB) did not differ significantly from the preoperative value (36.66 dB, P = .083). There were also minimal changes thereafter (45.63 dB) without recurrent case over an average follow-up time of 38.3 months (range, 17-69 months). More than 10 dB hearing loss was found in 7 patients with a case of intraoperative perilymph leakage (2.3%), although 5 of them had had preoperative air conduction threshold above 90 dB. Their fistulas were significantly larger than those of patients without hearing loss ( P = .027). Conclusion: Although caution is required for total removal of a large fistula, owing to increased risk of postoperative hearing deterioration, 1-stage complete resection of cholesteatoma matrix on labyrinthine fistula could be effective in disease control and long-term hearing preservation.